A country affair - Macomber, Debbie (Mira, 2021)
A little bit country: Stranded on the side of a country road with a broken-down car, Rorie Campbell is grateful when horse rancher Clay Franklin comes to her rescue. Stuck in the quirky small town, Rorie gets to know Clay, and she quickly starts to fall for the gruff, tough cowboy. Can a city girl make it work with a country man? Clay certainly thinks so. But their situation is... complicated. Clay and Rorie will have to sort out their feelings if they're going to be together.